2013
DOI: 10.1002/jgra.50386
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of wind, conductivity, and geomagnetic main field to the variation in the geomagnetic Sq field

Abstract: [1] Long-term variation in the geomagnetic Sq field and the cause of the variation were examined. The amplitude of the geomagnetic Y component (Sq(Y)) in equinox was averaged for each year and adopted as a proxy of the Sq field. Sq(Y) was combined with the ionospheric conductivity estimated by the International Reference Ionosphere model to determine the dynamo electric field and neutral wind velocity by using the geomagnetic main field strength. It was found that the solar activity dependence of the Sq field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 19 publications
2
37
0
1
Order By: Relevance
“…We take a rather simplified view of Takeda [] in order to understand our observational results. Takeda [] used a very simple expression for the magnitude ( A ) of the Y component geomagnetic daily variation on the basis of Fukushima 's [] model: A=34μ0normalΣUBz where μ 0 is the permeability of the vacuum (=4π×10 7 ), Σ is the effective ionospheric conductivity (S), U is zonal neutral wind speed (m s −1 ), and B z is the vertical geomagnetic field strength (nT). The constant 3/4 arises from the fact that the geomagnetic daily variation is produced not only by ionospheric currents but also by currents induced in the conductive Earth, which accounts for approximately 25% of the total effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We take a rather simplified view of Takeda [] in order to understand our observational results. Takeda [] used a very simple expression for the magnitude ( A ) of the Y component geomagnetic daily variation on the basis of Fukushima 's [] model: A=34μ0normalΣUBz where μ 0 is the permeability of the vacuum (=4π×10 7 ), Σ is the effective ionospheric conductivity (S), U is zonal neutral wind speed (m s −1 ), and B z is the vertical geomagnetic field strength (nT). The constant 3/4 arises from the fact that the geomagnetic daily variation is produced not only by ionospheric currents but also by currents induced in the conductive Earth, which accounts for approximately 25% of the total effect.…”
Section: Discussionmentioning
confidence: 99%
“…In light that the midlatitude ionospheric current system is subject to the Cowling effect [ Takeda , ], the effective ionospheric conductivity is given as follows: normalΣ=normalΣP+normalΣH2normalΣP where Σ P and Σ H are height‐integrated Pedersen and Hall conductivities, respectively. Takeda [] computed Σ P and Σ H using the International Reference Ionosphere model [ Bilitza , ; Bilitza et al , ]. He pointed out that the solar cycle variation in A is almost solely due to changes in Σ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, using long-term ionospheric conductivity and geomagnetic field data obtained at low-latitude stations, Takeda (2013) showed that solar activity effects cannot be clearly seen in the thermospheric neutral winds, which are derived from the Sq amplitude calculated from the Y component of the geomagnetic field. He pointed out that a major contribution of the solar activity effects on the Sq amplitude is not through the neutral wind velocity but instead through the height-integrated ionospheric conductivity.…”
Section: Elements To Determine the Sq Amplitudementioning
confidence: 99%
“…It is well known that the magnitude of the Sq variation has good correlation with solar activity indices such as sunspot numbers and the solar F10.7 index [e.g., Sellek 1980;Schlapp et al 1990;Macmillan and Droujinina 2007;Torta et al 2009;Elias et al 2010;Takeda 2013]. Sellek (1980) showed that the annual mean Sq amplitude obtained at San Juan at a low latitude is linearly proportional to the annual mean sunspot numbers using observation data during 1929 to 1965.…”
Section: Nonlinear Response Of the Sq Amplitude To The Solar F107 Indexmentioning
confidence: 99%